Fatty acid-binding protein 4 silencing protects against lipopolysaccharide-induced cardiomyocyte hypertrophy and apoptosis by inhibiting the Toll-like receptor 4–nuclear factor-κB pathway - Fangyuan Sun; Gang Chen; Yingyao Yang; Ming Lei (Journal of International Medical Research, 2021)
Objective To explore the effects and potential mechanisms of fatty acid-binding protein 4 (FABP4) in a lipopolysaccharide (LPS)-induced in vitro septic cardiomyopathy model. Methods Rat cardiomyocyte H9c2 cells were transfected with small interfering RNA (siRNA) against FABP4 (siFABP4), then induced with LPS. The following parameters were measured: cell viability, lactate dehydrogenase release, cardiac hypertrophy and related marker expression, apoptosis, inflammatory cytokine release and expression, and the activation of Toll-like receptor 4 (TLR4) and nuclear factor-κB (NF-κB) pathways. Results LPS increased the mRNA and protein expression of FABP4 in H9c2 cells. FABP4 silencing by siFABP4 significantly inhibited LPS-induced cardiac hypertrophy and reduced the mRNA expression of the myocardial hypertrophy markers atrial natriuretic peptide and brain natriuretic peptide. siFABP4 also attenuated LPS-induced increase in TUNEL-positive apoptotic cells, caspase-3 and caspase-9 activities, and the release and expression of proinflammatory cytokines. Mechanistically, we found that FABP4 silencing inhibited the mRNA and protein expression of TLR4 and suppressed the NF-kappa B signaling pathway, as evidenced by reduced nuclear NF-κB p65 and increased cytoplasmic I-κBα expression in LPS-stimulated H9c2 cells. Conclusion FABP4 silencing reduces LPS-induced cardiomyocyte hypertrophy and apoptosis by down-regulating the TLR4/NF-κB axis.